The vertical and horizontal distance of the starting point and the ball and relationship to the speed and accuracy skill of smash serve in volleyball - Jary, S. K.; Khalaf, K. A. A. (ResearchJet Journal of Analysis and Inventions, 2022)
Volleyball game is one of the games that consist of multiple, compound and somewhat difficult skills in some of its skills, especially the overwhelming skill A stage that contains mechanical variables that differ from the previous and subsequent stage, which gives it the characteristic of difficulty in terms of reaching the mechanism in the skill performance and the motor compatibility between the parts of the body and the surrounding stimuli, because of its importance in accessing high levels in the performance of the players and providing the effort made during the numbers, where The researchers used the descriptive curriculum in the method of survey studies and correlations of its suitability for the nature of the research problem, as it works to describe the performance variables without going through their experimentation. And by (5) players, the most important conclusions were: 1- The vertical distance from the starting point or from the level of the starting point affects the accuracy of the Smash Serve in volleyball . 2- The horizontal distance of the point of retention of the ball affects the speed of the start of the ball and the accuracy of the ball when performing the Smash Serve in volleyball.